2018
DOI: 10.3390/app8112117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Asphalt Mixes Behaviour from Dynamic Tests and Comparison with Conventional Cyclic Tension–Compression Tests

Abstract: In the presented research, conventional cyclic tension–compression tests and dynamic tests were performed on two types of asphalt mixes (AM). For the tension–compression tests, the complex modulus was obtained from the measurements of the axial stress and axial strain. For the dynamic tests, an automated impact hammer equipped with a load cell and an accelerometer were used to obtain the frequency response functions (FRFs) of the specimens at different temperatures. Two methods were proposed to back-calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The impact hammer was automated to improve the repeatability of the test and to allow measurements directly inside the thermal chamber. The order of magnitude of the maximum strain induced in the specimen by the impact is about 0.1 μm/m [8][9][10]. The response of the material was recorded with an accelerometer (PCB model 353B15) glued in the middle of the opposite short side of the specimen (see Fig.…”
Section: Experimental Measurement Of the Frequency Response Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact hammer was automated to improve the repeatability of the test and to allow measurements directly inside the thermal chamber. The order of magnitude of the maximum strain induced in the specimen by the impact is about 0.1 μm/m [8][9][10]. The response of the material was recorded with an accelerometer (PCB model 353B15) glued in the middle of the opposite short side of the specimen (see Fig.…”
Section: Experimental Measurement Of the Frequency Response Functionsmentioning
confidence: 99%
“…Carret et al [10] showed that the value of the Poisson's ratio has a very small influence on the FRFs calculation and that the norm and phase angle of the complex modulus can be determined from FRFs measurement at each temperature with a simple process described in Fig. 7.…”
Section: Complex Modulus From the First Resonance Peak Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing the 2S2P1D model, the master curve for the dynamic modulus of HMA can be established in the frequency domain [47,48]. Compared to the traditional complex modulus test, a new method that uses an automatic impact hammer, a load cell, and an accelerometer, is employed to measure the frequency response functions (FRFs) of HMA at various temperatures [49]. The complex modulus is then back-calculated from the measured FRFs, employing the 2S2P1D model and Williams-Landel-Ferry (WLF) function.…”
Section: Introductionmentioning
confidence: 99%